A Thermodynamic Model on a Linear Rule between the Molal Concentration Exponential and the Osmotic Coefficients on Mole Fraction Base in Electrolyte Solutions and its Application - Fang, Zheng (Journal of Applied Solution Chemistry and Modeling, 2015)
A linear rule is discovered. That is the osmotic coefficients on mole fraction base (ω) are linearly related to the molal concentration exponential (mk2) in single electrolyte solutions. Based on this rule, a thermodynamic model is developed and successfully used to the single electrolytes with various valent types, such as uniunivalent, biunivalent, triunivalent, tetraunivalent,bibivalent, andtribivalent to predict their conventional osmotic coefficients on molal base (ϕ), and also other properties, such as the relative molal vapor pressure lowering, the equivalent conductivity. Besides mk2, the xk2 (the concentration exponential of mole fraction of solute) mk2ln(mk2), and xk2ln(xk2) are also linearly related to ω, respectively. They are all capable to be used to reproduce some properties of single electrolyte solutions. The examples with satisfied results have been given.